2018
DOI: 10.15406/mojap.2018.05.00226
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acute or long-term genistein administration on the ischemia/reperfusion-induced arrhythmia in rats

Abstract: The cardiovascular disease and sudden death due to the occlusion of coronary artery increases in women after menopause. In this study, it was aimed to research the effect of genistein that has been used to decrease the symptom of menopause in women, on the ischemia reperfusion induced arrhythmias. 64 Female and 12 male, 6-7months old Sprague Dowley rats were used in this study. Genistein was applied daily for four weeks in 100ug/kg dose intraperitoneally in one group and acutely in other group, before reperfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…shows estrogenic effects and increases the contraction of myocardium (Bozdogan et al, 2018). Studies revealed that genistein reduces hypoxia-induced cardiac injuries.…”
Section: Ardioprotec Tive Ac Tivit Ymentioning
confidence: 99%
See 2 more Smart Citations
“…shows estrogenic effects and increases the contraction of myocardium (Bozdogan et al, 2018). Studies revealed that genistein reduces hypoxia-induced cardiac injuries.…”
Section: Ardioprotec Tive Ac Tivit Ymentioning
confidence: 99%
“…In postmenopausal women, level of estrogen declines which leads to the elevated risks of heart diseases (Thangavel et al, 2019). Several studies have revealed that genistein reduces the risk of cardiogenic diseases in women after the postmenopausal period because genistein is a phytoestrogen and possesses estrogen‐like properties, can bind with estrogen receptors (Bozdogan et al, 2018). Therefore, genistein reduces the menopausal symptoms, risk of heart failure and improves the cardiac function with minor or no adverse effects (Thangavel et al, 2019).…”
Section: Cardioprotective Activitymentioning
confidence: 99%
See 1 more Smart Citation